Response of peanut (Arachis hypogaea L.) genotypes to smut (Thecaphora frezii) in the peanut growing region of Argentina - Kearney, Marcelo Isaías; Zuza, Mónica Silvina; Ibañez, M.; Peralta, Vanesa Soledad; Peiretti, G.; Alcalde, M.; Mojica, C.; Rago, Alejandro Mario (American Peanut Research and Education Society, 2021)
Genetic resistance is the most efficient tool in crop disease management. Peanut smut is currently one of most important peanut diseases, with its incidence increasing in terms of both damage level and crop area covered. The aim of this study was to assess the response of different genotypes obtained by the Facultad de Agronomía y Veterinaria of the Universidad Nacional de Río Cuarto (Argentina) to smut and their yield. During the 2016/17, 2017/18 and 2018/19 crop seasons, three experimental assays were conducted in General Deheza (Córdoba province, Argentina) to evaluate the varieties Uchaima, Utré and Mapu, the advanced lines LAx-1, LAx-2, LAx-3 and LAx-4, and the cultivar Granoleico, which was used as susceptible control. Final incidence and severity of peanut smut, as well as kernel yield, were evaluated. The variety Utré and the advanced line LAx-1 exhibited the best response to smut over the three crop seasons, without differences between them, but differing significantly from the remaining genotypes. Both genotypes showed incidence below 6.8% and severity below 0.21. In the 2016/17 crop season, LAx-1 had the highest kernel yield (3791.6 kg/ha). In the 2017/18 and 2018/19 crop seasons, Utré had the highest yield (1065 and 3975 kg/ha). Kernel yield of susceptible genotypes was below 2851.6 kg/ha in the 2016/17 and 2018/19 crop seasons, and below 805 kg/ha in the 2017/18 crop season. Genotypes LAx-1 and Utré are resistant to peanut smut. This is the first report of a peanut commercial variety developed in Argentina (Utré) with confirmed tolerance to smut.